A theory‐informed qualitative exploration of social and environmental determinants of physical activity and dietary choices in adolescents with intellectual disabilities in their final year of school. (12th April 2017) - Stevens, Gemma; Jahoda, Andrew; Matthews, Lynsay; Hankey, Catherine; Melville, Craig; Murray, Heather; Mitchell, Fiona
Abstract : Background: The prevalence of obesity is higher in those with intellectual disabilities than the general population. The aim of the study was to understand the determinants of physical activity and dietary patterns in this population during their final year of school. Method: Qualitative data were generated from 10 interviews with adolescents with mild–moderate intellectual disabilities. Data were analysed using deductive thematic analysis, employing Self‐Determination Theory as a theoretical framework. Results: Adolescents' environment and social interactions play a pivotal role in influencing physical activity and dietary patterns. Three themes emerged from the analysis: situatedness, motivation and wider environmental influences. Conclusions: School structure, high self‐efficacy and social connectedness facilitate increased physical activity and healthier diet in adolescents with intellectual disabilities. Home life, low self‐efficacy and a lack of social connectedness can serve as a barrier to PA and a healthy diet.